Patterns of social participation and impacts on memory among the older people - Han, Hu; Hengyuan, Zhang; Yonggang, Tang (Frontiers in Public Health, 2022)
This study employs latent class analysis to analyze the social participation patterns of elderly Chinese, as well as the impact of different social participation patterns on memory. According to the results, older persons exhibit four distinct social participation patterns. and senior citizens with a strong emphasis on entertainment had a better memory than those with a low participation level. Although there was no difference in urban elders' memory across the four social engagement patterns, the connection varied significantly between urban and rural seniors. As a result, it is suggested that the elderly's memory be improved by protecting their right to social involvement, enriching the style and content of social participation, and assuring the continuity of their social obligations.